2014
DOI: 10.4314/tjpr.v13i11.2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of methyl jasmonate and silver nanoparticles on production of secondary metabolites by <i>Calendula officinalis</i> L (Asteraceae)

Abstract: Purpose: To investigate the effects of two elicitors, methyl jasmonat (MeJA) and silver nanoparticles (SNPs), on the production of secondary metabolite by Calendula officinalis L (marigold

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(31 citation statements)
references
References 18 publications
4
27
0
Order By: Relevance
“…31 The amount of saponin content in Calendula officinalis increased compared to the control roots after treatment with 0.4 mM nanosilver. 32 Due to the importance of the pharmaceutical and industrial applications of RA, its production has been studied in various plant species (Orthosiphon aristatus, Salvia miltiorrhiza, and Melissa officinalis) influenced by biological and non-biological elicitors. [33][34][35] In Agastache foeniculum hairy root cultures, a fourfold increase in RA content was observed.…”
Section: Introductionmentioning
confidence: 99%
“…31 The amount of saponin content in Calendula officinalis increased compared to the control roots after treatment with 0.4 mM nanosilver. 32 Due to the importance of the pharmaceutical and industrial applications of RA, its production has been studied in various plant species (Orthosiphon aristatus, Salvia miltiorrhiza, and Melissa officinalis) influenced by biological and non-biological elicitors. [33][34][35] In Agastache foeniculum hairy root cultures, a fourfold increase in RA content was observed.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is concern about their side effects on the environment, these can be minimized by limiting the concentration of nanoparticle solutions. The application of silver nanoparticles in Calendula officinalis resulted in a decrease in the anthocyanin and flavonoid contents and an increase in carotenoids and saponins [9]. The easy penetration of ultra-fine nanoparticles into the plant cell wall and vacuoles disturbs metabolic activity.…”
mentioning
confidence: 99%
“…For instance, the artemisinin content was increased in a hairy root culture of Artemisia annua upon treatment with core–shell silver nanoparticles . In Calendula officinalis , the anthocyanin and flavonoid contents were decreased, whereas carotenoid and saponin contents were increased in response to silver nanoparticles, as revealed by classical colorimetric assays . In addition, multiwalled carbon nanotubes stimulated the biosynthesis of secondary metabolites and the antioxidant capacity in the medicinal plant Satureja khuzestanica grown in vitro .…”
Section: Future Perspectivesmentioning
confidence: 98%
“…[95] In Calendula officinalis, the anthocyanin and flavonoid contents were decreased, whereas carotenoid and saponin contents were increased in response to silver nanoparticles, as revealed by classical colorimetric assays. [96] In addition, multiwalled carbon nanotubes stimulated the biosynthesis of secondary metabolites and the antioxidant capacity in the medicinal plant Satureja khuzestanica grown in vitro. [97] In the case of H. perforatum, one study has reported that zinc and iron nano-oxides stimulate hypericin and hyperforin production in cell suspension cultures.…”
Section: Future Perspectives Potential Application Of Nanotechnologymentioning
confidence: 99%